Mediating Religion and Government
XI, 264 p.
Keywords: The study of religion and politics is a strongly behavioral sub-discipline, and within the American context, scholars place tremendous emphasis on its influence on political attitudes and behaviors, resultuing in a better understanding of religion's ability to shape voting patterns, party affiliation, and views of public policy.